Bile Duct Injuries/Management With Jejunal Loop - A.G Rehan (Journal of University Medical & Dental College, 2020)
Bile duct injury during operation has been dilemma for surgeons for ages. It is surprising that how experienced surgeons can injure a bile duct while on the face of it, anatomy looks very easy. It is traumatic to the patient as well as to the surgeon who experiences many sleepless nights. These injuries are disastrous for both the patient and the surgeon because of the associated morbidity, prolonged hospitalization, and mortality.1 The patient is practically invalid till the complication is rectified. If the first surgeon declines to go in again, it is always better to get help from other surgeons. It is astonishing, with how much ease the injury occurs. The objective should be to diagnose the complication early and remedial procedure should be done earlier.